Decisions [ risk and reward - Bruce, Alistair; Johnson, Johnnie , 1952- (Routledge studies in business organizations and networks, 2008)
This book addresses a wide range of contemporary issues in decision research, such as how individuals deal with uncertainty and complexity, gender-based differences in decision-making, what determines decision performance and why people choose risky activities